Pragmatist Ethics for a Technological Culture
XXVI, 264 p.
Keywords: Our technological culture has an extremely dynamic character: old ways of reproducing ourselves, managing nature and keeping animals are continually replaced by new ones; norms and values with respect to our bodies, food production, health care and environmental protection are regularly being put up for discussion. This constantly confronts us with new moral problems and dilemmas. In discussion with other approaches this book argues that pragmatism, with its strong emphasis on the interaction between technology and values, gives us both procedural help and stresses the importance of living and cooperating together in tackling these problems and dilemmas. The issues in this book include the interaction of technology and ethics, the status of pragmatism, the concept of practice, and discourse ethics and deliberative democracy. It has an interactive design, with original contributions alternating with critical comments. The book is of interest for students, scholars and policymakers in the fields of bioethics, animal ethics, environmental ethics, pragmatist philosophy and science and technology studies.